In vitro propagation and phytochemical assessment of Perovskia abrotanoides Karel. (Lamiaceae) – A medicinally important source of phenolic compounds. (May 2019) - Ghaderi, Shahla; Nejad Ebrahimi, Samad; Ahadi, Hamid; Eslambolchi Moghadam, Sara; Mirjalili, Mohammad Hossein
Abstract: Perovskia abrotanoides Karel. (Lamiaceae) is an aromatic herb that is mainly grown in the mountains of Northeastern Iran across Northern Pakistan and Northwestern India. Here, a suitable system for regenerating P. abrotanoides via direct organogenesis was performed for the first time. In vitro -grown shoot tips were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations (1.0, 2.0, and 3.0 mg L −1 ) of kinetin (KN) and 6-benzylaminopurine (BAP) alone or in combination with two concentrations (0.5 or 1.0 mg L −1 ) of 2, 4-dichlorophenoxyacetic (2, 4-D), α-naphthalene acetic acid (NAA), and indole-3-butyric acid (IBA). MS medium supplemented with 3 mg L −1 BAP and 0.5 mg L −1 IBA with shoot proliferation percentage (83.3%) and shoot-forming capacity (SFC) index (5.5) was the optimal medium for shoot induction in the plant. Rooting of elongated shoots was performed on half-strength MS medium fortified with different concentrations (0.1, 0.5, and 1.0 mg L −1 ) of IBA, 2, 4-D, and NAA. The highest rooting percentage (100%) with a mean root number (5.9 ± 1.35) was obtained on the free-hormone medium. Rooted plantlets were successfully acclimatized in the greenhouse (75%) and transferred to natural conditions. Several phenolic acids were quantitatively determined in the extract of both in vitro regenerated plant (IVRP) and wild plant (WP). Rosmarinic acid was the most prominent phenolic acid in the extract of both samples. Total phenolic content of IVRP (70.7 ± 9.1 mg/g DW) was higher than WP (54.9 ± 15.2 mg/g DW). Antioxidant activity (IC50 ) of IVRP and WP extracts was 230.4 and 275.7 μg mL −1, respectively.